Central obesity and its associated factors among adults in Southwest Ethiopia - Asresash Sebeta; Eyob Tekalign; Tewodros Yosef (Elsevier, 2024)
Background: The rise of abnormal fat accumulation in the body's adipose tissue, termed obesity, poses a growing global public health concern. This study aimed to assess the prevalence of and associated factors of central obesity among adults in southwest Ethiopia. Methods: From May 23 to June 30, 2021, a community-based cross-sectional study involving 651 adults residing in Mizan-Aman Town was conducted. Central obesity was evaluated using the waist-to-hip ratio. Data were entered into Epi-Data version 3.1 and then exported to SPSS 22.0 for analysis. Logistic regression analysis was performed, with a significance level set at a p-value less than 0.05. Results: The prevalence of central obesity was 19.7 %. The study identified several factors associated with central obesity, including being male [adjusted odds ratio (AOR) = 0.28, 95 % CI: 0.18, 0.44], having a high wealth index [AOR = 1.77, 95 % CI: 1.07, 2.94], liquid oil consumption [AOR = 1.68, 95 % CI: 1.09, 2.58], and belonging to food-secured households [AOR = 0.27, 95 % CI: 0.18, 0.42]. Conclusion: The study's findings highlight a concerning prevalence of central obesity, affecting nearly one-fifth of the respondents. Sex, food security, wealth index, and liquid oil consumption were identified as factors associated with central obesity. These results emphasize the importance of implementing intervention programs aimed at preventing central obesity among adults, as this can also help prevent the development of other chronic diseases.